Integrating land use/land cover change with change in functional zones' boundary of the East Dongting Lake National Nature Reserve, China. (June 2022) - Xiao, Juan; Watanabe, Teiji; Lu, Xi; Chand, Mohan Bahadur; Umarhadi, Deha Agus; Chen, Xinyu; Avtar, Ram
Abstract: The boundaries of the East Dongting Lake National Nature Reserve's (EDLNNR) functional zones have been adjusted over time due to conditional changes. However, there is no systematic study being conducted on the EDLNNR's historical trend of land use/land cover (LULC). Therefore, it is crucial to understand the relationship between changes in functional zones' boundary and spatio-temporal changes in the LULC from pre-establishment to the present time for adequate protection. The objective of this study is to understand the spatio-temporal dynamics of LULC changes from 1979 to 2019 in the three functional zones of EDLNNR during the dry season. LULC transition matrix and landscape metrics at the landscape level were also used to investigate the land type dynamics and landscape fragmentation, respectively. An increase in the marsh area was observed in all three functional zones of EDLNNR. The built-up area was increased due to the conversion of agricultural land. The landscape metrics-based analysis showed that the EDLNNR was less fragmented in 2019 than the previous record in 2016, due to the adjustment action of the three functional zones' boundary of the EDLNNR in 2018. The excluded area of the EDLNNR was from its experimental zone, which includes densely populated areas and surrounding agricultural land and woodland. The spatio-temporal LULC change information can offer effective management and conservation of different functional zones of the EDLNNR. This study can also act as a case model for effective management of other protected areas worldwide. Highlights: LULC results reveal an increase in the marsh area in all three functional zones of EDLNNR. The landscape metrics results suggested that EDLNNR is less fragmented in 2019 than in 2016. Reed harvesting activities are noticed to be existing in the core zone and buffer zone.